Self-reaction type solid-waste-based road base material with uniform and dense structure and preparation method of self-reaction type solid-waste-based road base material
By using aggregates such as granite stone powder, phosphogypsum, fly ash and cinder in the road base materials, combined with the chemical reaction of interface modifiers, the problem of poor stability of uniform and dense structural materials in traditional technology is solved, and high Preparation of solid waste-based road base materials with performance and environmental protection.
Patent Information
- Application Number
- CN202411426294.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-10
AI Technical Summary
The structure formation method of traditional gelling materials + aggregates cannot prepare stable uniform and dense structure road base materials, and the increase in the amount of gelling materials increases the risk of cracking. Adding functional admixtures will cause ecological environment pollution.
The self-reactive uniform and dense structure solid waste base road base material is used, granite stone powder, phosphogypsum, fly ash and cinder are used as aggregates, combined with a small amount of cement and interface modifiers, and the components are enhanced through chemical reactions. The force to achieve the stability and strength of the material.
Through the synergy of multiple chemical reactions, the stability and strength of the material are significantly improved, the dependence on external gelling materials is reduced, the material preparation process is simplified, and the materials used are all renewable biological resources and are environmentally friendly.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a self-reactive uniformly dense structure solid waste-based road base material and a preparation method thereof. Background Art
[0002] The use of solid waste to prepare road base materials has been considered an effective way to dispose of large amounts of solid waste. The commonly used structure formation method is cementitious material + aggregate. In this method, the two materials have a clear division of labor, that is, the cementitious material provides bonding and the aggregate provides support. According to the content of coarse aggregate and fine aggregate (with 4.75mm as the dividing line) in the road base material, the structural state of traditional road base materials is divided into skeleton dense structure, skeleton pore structure, suspended dense structure and uniform dense structure. Among them, the road base materials prepared with skeleton dense structure and skeleton pore structure have excellent performance and are the most widely used structures in engineering. However, both of the above structures have specific requirements for the gradation of aggregates, which leads to the need to design specific gradation calculation methods when preparing road base materials using different types of solid waste, and high requirements for the particle size of solid waste. Unlike the skeleton dense structure and the skeleton pore structure, there is no coarse aggregate with a particle size greater than 4.75 mm in the uniform dense structure. Therefore, there is no need to design the aggregate grading, and the particle size requirements for solid waste are low. However, since the structure is composed entirely of fine aggregates, when the traditional structure formation method is used in the preparation process of the material, it is easy to cause uneven dispersion of the cementitious material, resulting in poor material stability.
[0003] At present, the most common method to improve the stability of uniform and dense structural solid waste-based road base materials is to increase the amount of cementitious materials, but the increase in the amount of cementitious materials will increase the risk of cracking of the base materials. In addition to increasing the amount of cementitious materials, some scholars have improved the stability of the base materials by adding admixtures with special functions. For example, patent CN116924740A enhances the mechanical properties of the material by adding three admixtures: ion curing agent, early strength agent and anti-hard water agent during the preparation of red mud-graphite tailings road base materials. However, in the process of preparing the admixture, chemical reagents with different acidity and alkalinity are involved. During the use of the base material, the various ions contained in the admixture will penetrate into the surrounding soil with rainwater, causing harm to the ecological environment.
[0004] In summary, the traditional cementitious material + aggregate structure formation method cannot prepare road base materials with stable performance and uniform and dense structure. Increasing the amount of cementitious materials will easily increase the risk of cracking and carbon emissions, and adding functional admixtures will easily cause ecological and environmental pollution. Therefore, how to use fine-grained solid waste to prepare stable performance and uniform and dense structural road base materials to improve the comprehensive utilization efficiency of solid waste has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a self-reactive uniform and dense structure solid waste-based road base material and a preparation method thereof in view of the shortcomings of the prior art. Granite powder, phosphogypsum, original fly ash and coal slag are used as aggregates, and a small amount of cement is used as a cementitious material. An interface modifier is combined. Based on the synergistic effect of aggregate modification, cementation and aggregate self-reaction, the interaction force between the components in the base material is enhanced through chemical reaction, thereby changing the traditional preparation method of relying solely on cementitious materials to consolidate aggregates, and realizing the preparation of uniform and dense structure solid waste-based road base materials.
[0006] In order to solve the technical problem raised by the present invention, the present invention provides a self-reactive uniformly dense structure solid waste-based road base material, including the following raw materials in parts by weight: 100 parts of solid waste-based aggregate, 3 to 5 parts of cement, 5 to 7 parts of interface modifier, and the moisture content is controlled to be 14 to 19%.
[0007] In the above scheme, the solid waste-based aggregate includes the following raw materials in percentage by mass: 50-60% granite powder, 20-30% phosphogypsum, 5-10% fly ash, and 10-15% coal slag.
[0008] In the above scheme, the particle size of the solid waste-based aggregate is ≤4.75mm.
[0009] Furthermore, the granite powder is waste powder in a naturally accumulated state, and has a moisture content of ≤13%.
[0010] Furthermore, the phosphogypsum is original phosphogypsum, the chemical composition of which is mainly CaSO4·2H2O, and the water content is less than 25%.
[0011] Furthermore, the fly ash is original fly ash collected by dust removal equipment, without any treatment before use, and has a moisture content of ≤13%.
[0012] Furthermore, the coal-fired slag comes from the ash deposited on the furnace bottom or furnace wall during the coal combustion process, and has a moisture content of ≤13%.
[0013] In the above scheme, the preparation method of the interface modifier comprises the following steps:
[0014] 1) Dissolve calcium chloride and urea in water and stir evenly to form a mixed solution A;
[0015] 2) Mixing the mixed solution A and the soybean urease solution and stirring them evenly to obtain a mixed solution B;
[0016] 3) adding quaternized chitosan and sodium alginate into water, heating and stirring to react, to obtain a mixed solution C;
[0017] 4) Mix the mixed solution B and the mixed solution C and stir them evenly to obtain an interface modifier.
[0018] Furthermore, in step 1), the weight percentages of the raw materials used are: 5-10 parts of calcium chloride, 1-5 parts of urea, and 80-90 parts of water.
[0019] Furthermore, the concentration of soybean urease in the soybean urease solution is 10-20 g / L.
[0020] Furthermore, the volume ratio of the mixed solution A to the soybean urease solution is 1:(1-1.5).
[0021] Furthermore, in step 3), the weight proportions of the raw materials used are: 10-20 parts of quaternized chitosan, 5-10 parts of sodium alginate, and 70-80 parts of water.
[0022] Furthermore, in step 3), the temperature is raised to 75-85° C. and the reaction is stirred for 2.5-3.5 hours.
[0023] Furthermore, the volume ratio of the mixed solution B to the mixed solution C is 1:(1.5-2.5).
[0024] Furthermore, the molecular weight of the quaternized chitosan is 100-300 kDa, preferably 100 kD or 300 kDa, the degree of deacetylation is 60-80%, and the degree of substitution is 40-50%.
[0025] In the above scheme, the cement is ordinary Portland cement with a strength grade of 32.5 and above.
[0026] In the above solution, the moisture content of the road base material is preferably 15-17%.
[0027] The present invention also provides a method for preparing a self-reactive uniformly dense structure solid waste-based road base material, comprising the following steps:
[0028] 1) Calculate the amount of added water based on the moisture content of each raw material and the set moisture content of the road base material;
[0029] 2) According to the amount of added water, water is evenly sprayed onto the surface of the granite powder of the solid waste-based aggregate, and then evenly mixed with the interface modifier and sealed for reaction to obtain modified granite powder;
[0030] 3) The modified granite powder is uniformly mixed with cement, phosphogypsum, fly ash and coal slag to obtain a mixture, and the mixture is filled into a mold and compacted to obtain a road base material.
[0031] In the above scheme, the sealing reaction time is 3 to 4 hours.
[0032] In the above solution, the compaction degree of the road base material is 90-98%.
[0033] Furthermore, the compaction degree of the road base material is preferably 95-97%.
[0034] The technical concept of the present invention is as follows:
[0035] The purpose of the present invention is to prepare a uniform and dense structural road base material with stable performance from solid waste with a particle size of less than or equal to 4.75 mm through the screening, design and optimization of material components. The specific design idea is to introduce a modifier on the one hand to improve the surface properties of inert aggregate particles and enhance their chemical reaction activity, and on the other hand to optimize the type of aggregate so that the aggregates are closely combined through chemical reactions under external stimulation conditions, thereby reducing the dependence on externally added cementitious materials. The following 6 chemical reactions are involved:
[0036] (1) Ion replacement: Granite powder aggregates have stable performance and low hydration reaction activity. At the same time, the particles are mainly surrounded by monovalent ions such as sodium and potassium. The surface of the particles is mostly double-electron layer with a thick electric layer thickness, which hinders the agglomeration and bonding of granite powder particles with other materials. It is modified by an interfacial modifier. Under the action of soybean urease catalyst, part of the calcium ions in the interfacial modifier replace the monovalent ions such as sodium and potassium on the surface of the stone powder particles through ion replacement, changing the double electric layer into a single electric layer, reducing the electric layer thickness of the stone powder particles, and providing a basis for the agglomeration and bonding of the stone powder particles with other materials.
[0037] (2) Salting out: The calcium ions in the interfacial modifier precipitate the organic matter in the soybean urease through salting out, increasing the viscosity of the solution and helping to enhance the bonding effect of the particles.
[0038] (3) Carbonization: During the forming and curing process of the base material, the calcium ions in the solution react with the carbonate ions produced by the hydrolysis of urea and the carbon dioxide in the air to generate calcium carbonate through carbonization.
[0039] (4) Hydration reaction: There are two main types of hydration reactions involved in this patent. The first is the hydration reaction of cement in a water environment to generate hydration products such as hydrated calcium silicate gel and calcium hydroxide; the second is the reaction of sulfate ions contained in phosphogypsum aggregate with the hydration product calcium hydroxide to generate calcium sulfonate crystals.
[0040] (5) Pozzolanic reaction: There are two main types of pozzolanic reactions involved in this patent. The first is that under the stimulation of the alkaline environment generated by cement hydration, the low-activity coal slag and the surface layer of the original fly ash in the solid waste aggregate produce some active Si 4+ and Al 3 + ions, reacting with free calcium ions in the solution to form hydrated calcium silicate gel. 4+ and Al 3+The ions react with the calcium ions attached to the surface of the stone powder particles through ion replacement to form hydrated calcium silicate gel, which improves the bonding force between the stone powder particles and the coal slag and fly ash.
[0041] (6) Charge interaction: Quaternized chitosan and sodium alginate are positively charged and negatively charged, respectively. There are two types of charge interactions in the system: one is the charge interaction between particles with positive charges on the surface. This reaction causes sodium alginate to adhere to the surface of some stone powder particles, coal slag and original fly ash. The other is the charge interaction between polymers with opposite charges. This reaction involves the reaction of quaternized chitosan in the solution with sodium alginate on the surface of the aggregate, thereby pulling the stone powder particles, coal slag and original fly ash together and improving the bonding force between the particles.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) The chitosan, alginate and soybean urease selected in the interface modifier prepared by the present invention are typical biological resources on the earth and are all renewable. Calcium chloride and urea do not contain heavy metal ions. The above materials are widely used in various biological systems and are environmentally friendly. The prepared road base material aggregates are all composed of solid waste with a particle size of less than or equal to 4.75 mm. By introducing modifiers, the surface properties of inert aggregate particles are improved and their chemical reaction activity is enhanced. By optimizing the types of aggregates, the aggregates are closely combined through chemical reactions under external stimulation conditions, thereby reducing the dependence on externally added cementitious materials. The above method makes the prepared base material have better stability, omits the traditional base material grading design steps, and simplifies the material preparation process on the basis of ensuring material performance.
[0044] (2) The present invention starts from the perspective of the curing mechanism of road base materials, and solves the problem of poor stability of road base materials with uniform and dense structures by constructing multiple synergistic reactions between cementitious materials and aggregates. For inactive granite stone powder particle aggregates, ion replacement occurs with the interface modifier to weaken the thickness of the surface electrical layer of the particles, reduce the distance between particles, and ionize the surface of the particles to prepare for subsequent speaking reactions. At the same time, calcium ions increase the viscosity of the solution and the bonding force between particles by salting out the organic matter in the soybean crude enzyme. For gypsum, coal slag and original fly ash fine aggregates, on the one hand, in the alkaline environment generated by cement hydration, the surface of coal slag and original fly ash fine aggregates produces active Si 4+ 、Al 3+Ions react with calcium ions around stone powder particles through volcanic ash to form calcium silicate gel. This process allows the bonding between fine aggregates to be achieved through spontaneous chemical reactions, significantly improving the bonding force between particles. On the other hand, gypsum reacts with hydration products to form calcium aluminate crystals with expansion effect, which has a reinforcing effect on the strength and stability of the material, further improving the strength of the material. In addition, the stone powder particles surrounded by calcium ions and the surface layer produce active Si 4+ 、Al 3+ The ionic coal slag and fly ash react with quaternized chitosan and sodium alginate, and through charge interaction, the ionic attraction effect is used to further improve the particle interface bonding performance. Finally, the free calcium ions in the system will also form calcium carbonate crystals in the internal gaps of the base material through carbonization during the material curing and molding process, further improving the density of the base material. Under the joint action of the above-mentioned synergistic reactions, the preparation of a new type of uniform and dense structure road base material is achieved through the ionic / chemical action between multiple components. DETAILED DESCRIPTION
[0045] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0046] In the following embodiments, the particle size of the solid waste-based aggregate used is ≤4.75mm; the granite powder is waste powder in a naturally accumulated state, and its moisture content is 10.5%; the phosphogypsum is original phosphogypsum, the chemical composition is mainly CaSO4·2H2O, and its moisture content is 21.3%; the fly ash is original fly ash collected by dust removal equipment, which is not treated before use, and its moisture content is 9.4%; the coal slag comes from the ash deposited on the bottom or wall of the furnace during the combustion of coal, and its moisture content is 10.7%.
[0047] In the following examples, the cement used is ordinary Portland cement with a strength grade of 42.5; the molecular weight of the quaternized chitosan used is 300 kDa, the degree of deacetylation is 60%, and the degree of substitution is 40%.
[0048] Example 1
[0049] In this embodiment, the self-reactive uniformly dense structure solid waste-based road base material includes the following raw materials in proportion by mass: 100 parts of solid waste-based aggregate, 4 parts of cement, 6 parts of interface modifier, and the moisture content is controlled to be 16%; wherein, the solid waste-based aggregate includes the following raw materials in proportion by mass: 60% granite powder, 20% phosphogypsum, 10% fly ash, and 10% coal slag.
[0050] In this embodiment, the preparation method of the interface modifier comprises the following steps:
[0051] 1) dissolving 7 parts by mass of calcium chloride and 3 parts by mass of urea in 80 parts by mass of water and stirring uniformly to form a mixed solution A;
[0052] 2) Mixing the mixed solution A and a soybean urease solution having a concentration of 15 g / L in a volume ratio of 1:1 and stirring the mixture to obtain a mixed solution B;
[0053] 3) adding 10 parts by weight of quaternized chitosan and 10 parts by weight of sodium alginate to 80 parts by weight of water, heating to 80° C. and stirring for reaction for 3 hours to obtain a mixed solution C;
[0054] 4) Mix the mixed solution B and the mixed solution C in a volume ratio of 1:2 and stir them evenly to obtain an interface modifier.
[0055] In this embodiment, the method for preparing a self-reactive uniformly dense structure solid waste-based road base material comprises the following steps:
[0056] 1) Calculate the amount of added water based on the moisture content of each raw material and the set moisture content of the road base material;
[0057] 2) According to the amount of added water, water is evenly sprayed onto the surface of the granite powder of the solid waste-based aggregate, and then evenly mixed with the interface modifier and sealed for reaction for 3.5 hours to obtain modified granite powder;
[0058] 3) The modified granite powder is uniformly mixed with cement, phosphogypsum, fly ash and coal slag to obtain a mixture, and the mixture is filled into a mold and compacted to form a road base material with a compaction degree of 95%.
[0059] Example 2
[0060] In this embodiment, the self-reactive uniformly dense structure solid waste-based road base material includes the following raw materials in proportion by mass: 100 parts of solid waste-based aggregate, 4 parts of cement, 6 parts of interface modifier, and the moisture content is controlled to be 16%; wherein, the solid waste-based aggregate includes the following raw materials in proportion by mass: 55% of granite powder, 25% of phosphogypsum, 10% of fly ash, and 10% of coal slag.
[0061] In this embodiment, the preparation method of the interface modifier comprises the following steps:
[0062] 1) dissolving 9 parts by mass of calcium chloride and 4 parts by mass of urea in 86 parts by mass of water and stirring uniformly to form a mixed solution A;
[0063] 2) Mixing the mixed solution A and a soybean urease solution having a concentration of 18 g / L at a volume ratio of 1:1.5 and stirring the mixture to obtain a mixed solution B;
[0064] 3) adding 15 parts by weight of quaternized chitosan and 8 parts by weight of sodium alginate to 73 parts by weight of water, heating to 85° C. and stirring for reaction for 2.5 hours to obtain a mixed solution C;
[0065] 4) Mix the mixed solution B and the mixed solution C in a volume ratio of 1:2.5 and stir them evenly to obtain an interface modifier.
[0066] In this embodiment, the method for preparing a self-reactive uniformly dense structure solid waste-based road base material comprises the following steps:
[0067] 1) Calculate the amount of added water based on the moisture content of each raw material and the set moisture content of the road base material;
[0068] 2) According to the amount of added water, water is evenly sprayed onto the surface of the granite powder of the solid waste-based aggregate, and then evenly mixed with the interface modifier and sealed for reaction for 3.8 hours to obtain modified granite powder;
[0069] 3) The modified granite powder is uniformly mixed with cement, phosphogypsum, fly ash and coal slag to obtain a mixture, and the mixture is filled into a mold and compacted to form a road base material with a compaction degree of 97%.
[0070] Example 3
[0071] The difference between this embodiment and embodiment 1 is only that: the amount of raw materials used in the solid waste-based aggregate is different;
[0072] In this embodiment, the solid waste-based aggregate includes the following raw materials in percentage by mass: 50% granite powder, 30% phosphogypsum, 10% fly ash, and 10% coal slag.
[0073] Example 4
[0074] The difference between this embodiment and embodiment 1 is only that: the amount of raw materials used in the solid waste-based aggregate is different;
[0075] In this embodiment, the solid waste-based aggregate includes the following raw materials in percentage by mass: 60% granite powder, 20% phosphogypsum, 5% fly ash, and 15% coal slag.
[0076] Example 5
[0077] The difference between this embodiment and embodiment 1 is only that: the amount of raw materials used in the solid waste-based aggregate is different;
[0078] In this embodiment, the solid waste-based aggregate includes the following raw materials in percentage by mass: granite powder 60%, phosphogypsum 20%, fly ash 8%, and coal slag 12%.
[0079] Example 6
[0080] The difference between this embodiment and embodiment 1 is only that: the amount of raw materials used in the road base material is different;
[0081] In this embodiment, the road base material includes the following raw materials in parts by weight: 100 parts of solid waste-based aggregate, 3 parts of cement, and 7 parts of interface modifier, and the moisture content is controlled to be 16%.
[0082] Example 7
[0083] The difference between this embodiment and embodiment 1 is only that: the amount of raw materials used in the road base material is different;
[0084] In this embodiment, the road base material includes the following raw materials in parts by weight: 100 parts of solid waste-based aggregate, 5 parts of cement, and 5 parts of interface modifier, and the moisture content is controlled to be 16%.
[0085] Example 8
[0086] The difference between this embodiment and embodiment 1 is only that: the amount of raw materials used in the road base material is different;
[0087] In this embodiment, the road base material includes the following raw materials in parts by weight: 100 parts of solid waste-based aggregate, 4 parts of cement, and 6 parts of interface modifier, and the moisture content is controlled to be 19%.
[0088] Comparative Example 1
[0089] The difference between this comparative example and Example 1 is that calcium chloride is not used in the preparation process of the interface modifier, that is, urea is dissolved in water to form a mixed solution A in step 1).
[0090] Comparative Example 2
[0091] The difference between this comparative example and Example 1 is that soybean urease solution is not used in the preparation process of the interfacial modifier, that is, step 2) is not performed, and in step 4), mixed solution A and mixed solution C are mixed to obtain the interfacial modifier.
[0092] Comparative Example 3
[0093] The difference between this comparative example and Example 1 is that no quaternized chitosan is used in the preparation of the interfacial modifier, that is, in step 3), sodium alginate is added to water and the temperature is raised to react to obtain a mixed solution C.
[0094] Comparative Example 4
[0095] The difference between this comparative example and Example 1 is that sodium alginate is not used in the preparation process of the interfacial modifier, that is, in step 3), quaternary ammonium chitosan is added to water and heated to react to obtain a mixed solution C.
[0096] Comparative Example 5
[0097] The only difference between this comparative example and Example 1 is that no interface modifier is used in the raw materials of the road base material.
[0098] Comparative Example 6
[0099] The difference between this comparative example and Example 1 is that no interface modifier is used in the raw materials of the road base material, and the mass fraction of cement is adjusted to 10 parts.
[0100] Comparative Example 7
[0101] The only difference between this comparative example and Example 1 is that no cement is used in the raw materials of the road base material.
[0102] Comparative Example 8
[0103] The difference between this comparative example and Example 1 is that cement is not used in the raw materials of the road base material, and the mass fraction of the interface modifier is adjusted to 10 parts.
[0104] Comparative Example 9
[0105] The only difference between this comparative example and Example 1 is that no interface modifier is used in the raw materials of the road base material, the mass fraction of cement is adjusted to 10 parts, and the solid waste-based aggregate is 100% granite powder.
[0106] The above embodiments and comparative examples were tested for performance according to the relevant specifications and test procedures in the standard JTG E51-2009 "Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering". The main tested performances include: unconfined compressive strength (7d, 14d, 28d), splitting tensile strength (7d) and softening coefficient. The softening coefficient test method is to soak the specimen in water for 12 days after standard curing for 7 days, and calculate the ratio of the compressive strength of the immersed specimen to the compressive strength of the standard cured specimen. The result is the softening coefficient of the material. The results are shown in the following table.
[0107] Table 1 Road base material performance test results
[0108]
[0109] From the test results of Examples 1 to 8, it can be seen that the 7d unconfined compressive strength of the road base material prepared with all fine powder exceeds 5.0MPa, and the 28d unconfined compressive strength is close to 10MPa, which meets the use requirements of heavy traffic on expressways and first-class highways and extremely heavy traffic on second-class and below highways. The splitting tensile strength of Examples 1 to 8 all reaches 0.6MPa and above. After 12 days of continuous immersion in water, the softening coefficient of the material exceeds 160%, proving that the compressive strength of the test piece is not lost after immersion in water, and the test piece has a strong ability to resist immersion in water. This result shows that under the synergistic effect of multiple effects, the road base material prepared by the present invention effectively solves the problem of poor performance of traditional uniform and dense structure road base materials.
[0110] The results of Comparative Examples 1 to 4 show that when a certain component is missing in the interface modifier, the performance of the material will be significantly affected. When calcium chloride is missing (Comparative Example 1), ion exchange and salting-out cannot be performed, resulting in a thicker double electrical layer of the particles, a decrease in particle agglomeration, and the surface of the stone powder particles cannot be bonded with the active Si 4+ 、Al 3+ The ions undergo hydration reaction, and the bonding force between the stone powder particles and other materials decreases, resulting in reduced material performance. When soybean urease is missing (Comparative Example 2), due to the lack of catalysis, the ion replacement reaction speed is slow, and the particle electrical layer thickness decreases slowly, resulting in reduced material performance. However, since the ion replacement effect still exists, the performance of Comparative Example 2 is slightly higher than that of Comparative Example 1. When quaternized chitosan is missing (Comparative Example 3), charge interactions between oppositely charged polymers cannot be carried out between particles, but since other reactions can proceed on their own, the performance of this comparative example is lower than that of Example 1. When sodium alginate is missing (Comparative Example 4), the stone powder particles with positive charges on the surface cannot interact with sodium alginate, thereby affecting the polymer charge interaction with quaternized chitosan. The bonding of the stone powder particles mainly relies on hydration, which makes the strength of this example significantly lower than that of Example 1, proving that sodium alginate has a greater impact on material strength. The above results further prove that the material preparation method proposed in the present invention is based on the synergistic effect of multiple reactions, which helps to improve the performance of fine aggregate road base materials.
[0111] The difference between Comparative Examples 5 and 6 and Example 1 is that no interfacial modifier is added. The results show that the mechanical properties and softening coefficient of the materials are significantly reduced. Under this ratio, the bonding between the particles of the materials mainly depends on cement hydration and a small amount of volcanic ash reaction. Due to the lack of ion replacement, salting-out reaction and charge interaction, the material performance is reduced. However, since the amount of cement used in Comparative Example 6 is higher than that in Comparative Example 5, the performance of Comparative Example 6 is slightly higher than that of Comparative Example 5.
[0112] The difference between Comparative Examples 7 and 8 and Example 1 is that no cement is added. Compared with Example 1, due to the lack of hydration reaction, the performance of Comparative Examples 7 and 8 is lower than that of Example 1. In addition, the performance of Comparative Examples 7 and 8 is close to that of Comparative Examples 5 and 6, proving that the interface modifier prepared by the present invention also has a certain gelling property, and further proving that the performance improvement of the material of the present invention is achieved based on the synergistic effect of multiple reactions.
[0113] The difference between Comparative Example 9 and Example 1 is that only granite powder and cement are used in the preparation. The results show that the performance of the material is significantly lower than that of Example 1. It is worth noting that the performance of Comparative Example 6 is better than that of Comparative Example 9, which proves that the spontaneous pozzolanic reaction of aggregate helps to improve the bonding strength of aggregate and enhance the performance of the material.
[0114] The above results prove that the interface modifier prepared by the present invention is helpful to optimize the material properties. In the presence of a small amount of cement and the interface modifier, the comprehensive performance of the road base material with uniform and dense structure is significantly improved through the synergistic effect of ion replacement, salting out, carbonization, hydration reaction, volcanic ash reaction and charge interaction, thereby realizing the preparation of low-carbon green solid waste-based road base materials.
[0115] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A self-reactive uniformly dense structure solid waste-based road base material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of solid waste-based aggregate, 3-5 parts of cement, and 5-7 parts of interface modifier, and the moisture content is controlled to be 14-19%. The solid waste-based aggregate comprises the following raw materials in percentage by weight: 50-60% of granite powder, 20-30% of phosphogypsum, 5-10% of fly ash, and 10-15% of coal slag. The preparation method of the interface modifier comprises the following steps: 1) Dissolve calcium chloride and urea in water and stir evenly to form a mixed solution A; 2) Mixing the mixed solution A and the soybean urease solution and stirring them uniformly to obtain a mixed solution B; 3) adding quaternized chitosan and sodium alginate into water, heating and stirring to react, to obtain a mixed solution C; 4) Mixing the mixed solution B and the mixed solution C and stirring them uniformly to obtain an interfacial modifier.
2. The self-reactive uniformly dense structure solid waste-based road base material according to claim 1, characterized in that: The particle size of the solid waste-based aggregate is ≤4.75mm.
3. The self-reactive uniformly dense structure solid waste-based road base material according to claim 1, characterized in that: The moisture content of the granite powder is ≤13%; the moisture content of the phosphogypsum is <25%; the moisture content of the fly ash is ≤13%; the moisture content of the coal slag is ≤13%; the cement is ordinary Portland cement with a strength grade of 32.5 or above.
4. The self-reactive uniformly dense structured solid waste-based road base material according to claim 1, characterized in that: The mixed solution A is composed of the following raw materials in parts by mass: 5 to 10 parts of calcium chloride, 1 to 5 parts of urea, and 80 to 90 parts of water.
5. The self-reactive uniformly dense structured solid waste-based road base material according to claim 1, characterized in that: The concentration of soybean urease in the soybean urease solution is 10-20 g / L; the volume ratio of the mixed solution A to the soybean urease solution is 1:(1-1.5).
6. The self-reactive uniformly dense structure solid waste-based road base material according to claim 1, characterized in that: In step 3), the weight proportions of the raw materials used are: 10-20 parts of quaternized chitosan, 5-10 parts of sodium alginate, and 70-80 parts of water. The temperature is raised to 75-85° C. and stirred for reaction for 2.5-3.5 hours.
7. The self-reactive uniformly dense structured solid waste-based road base material according to claim 6, characterized in that: The molecular weight of the quaternized chitosan is 100-300 kDa, the deacetylation degree is 60-80%, and the substitution degree is 40-50%.
8. The self-reactive uniformly dense structured solid waste-based road base material according to claim 1, characterized in that: The volume ratio of the mixed solution B to the mixed solution C is 1:(1.5-2.5).
9. The method for preparing a self-reactive uniformly dense structured solid waste-based road base material according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) Calculate the amount of added water based on the moisture content of each raw material and the set moisture content of the road base material; 2) spraying water evenly onto the surface of the granite powder of the solid waste-based aggregate according to the amount of water added, then mixing it evenly with the interfacial modifier and sealing it for reaction to obtain modified granite powder; 3) The modified granite powder is uniformly mixed with cement, phosphogypsum, fly ash and coal slag to obtain a mixture, and the mixture is filled into a mold and compacted to obtain a road base material.
10. The method for preparing a self-reactive, uniformly dense structured solid waste-based road base material according to claim 9, characterized in that: The sealing reaction time is 3 to 4 hours; and the compaction degree of the road base material is 90 to 98%.
Citation Information
Cited By
Large-flow-state coal-based solid waste filling material as well as preparation method and application thereof
CN121159220A